Czy chłop miał honor? Zastosowanie kategorii honoru w badaniach nad społeczeństwem nowożytnym - Korczak-Siedlecka, Jaśmina (Kwartalnik Historyczny, 2019)
Artykuł szuka odpowiedzi na pytania o znaczenie honoru i możliwe sposoby jego interpretacji, a także o przydatność tej kategorii w badaniach historycznych. Refleksje teoretyczne zostały uzupełnione analizą wiejskich ksiąg sądowych z terenu Mierzei Wiślanej z przełomu XVI/XVII w., dowodzącą kluczowej roli honoru w ówczesnych społecznościach chłopskich. The article seeks to answer the questions about the meaning of honour and its possible interpretations, together with that about the usefulness of this category in historical studies. The theoretical reflections are reinforced with an analysis of village court registers from the area of the Vistula Spit at the turn of the seventeenth century which proves the key role of honour within contemporary peasant communities.